Analisis Kemampuan Berpikir Kritis Matematis Siswa pada Distribusi Peluang Binomial Ditinjau dari Jenis Kelamin - Laila Akbar Ramadhany; Sutrisno Sutrisno; Solastri Solastri (Institut Agama Islam Negeri Curup, 2023)
Entering the 21st century, having 21st century capabilities is very necessary to be able to answer all the challenges that are present in this century. One of the abilities of the 21st century is the ability to think critically. One of the factors that influences critical thinking skills is gender. Therefore, this research aims to use qualitative descriptive research techniques to describe students' mathematical critical thinking abilities, especially in the material on binomial probability distribution. The research subjects were taken using a purposive sampling technique, namely 4 students were selected, namely 2 male students and 2 female students in class XII MIPA 1 MAN 1 Semarang City. Considerations for selecting research subjects are seen from students' daily mathematics scores, students' gender, students' responses when learning mathematics. The data collection technique used in this research is the test method. The form of test used is an essay test. The data analysis technique is carried out through data reduction followed by data presentation and drawing conclusions. The data validity test was carried out through triangulation of data sources based on gender, namely male and female. The results of this research show that there are significant differences in analysis and inference indicators related to mathematical critical thinking abilities between male and female research subjects.